EFFECT OF RED DRAGON FRUIT (HYLOCEREUS POLYRHIZUS) PEEL ETHANOL EXTRACT ON VAGINAL WALL COLLAGEN EXPRESSION IN MENOPAUSE MODEL RATS - Rahcmanita, Dhila Cahya; Sugiritama, I Wayan; Ratnayanti, I Gusti Ayu Dewi; Wahyuniari, Ida Ayu Ika (E-Jurnal Medika Udayana; Vol 12 No 6 (2023): E-Jurnal Medika UdayanaDO - 10.24843/MU.2023.V12.i06.P16, 2023)
The skin of red dragon fruit ( Hylocereus polyrhizus ) contains polyphenols, in particular anthocyanins, which may act as phytoestrogens and antioxidants. Phytoestrogens can help synthesize collagen through their bonds with estrogen receptors and antioxidants prevent the accumulation of free radicals that can damage collagen, so the skin of red dragon fruit has the potential to prevent vaginal organ disorders due to the reduced amount of collagen in the vaginal wall during menopause. This study aims to prove the effectiveness of the ethanol extract of Hylocereus polyrhizus rind in preventing decreased collagen in the vaginal wall of menopausal rats. This study was structured using a randomized post-test only control group design on 30 female Wistar rats, which were divided into three groups, namely the control group (P0) was given normal saline, the treatment group (P1) was given ethanol extract 60mg/200grBW and (P2) was given ethanol extract 90mg/200grBB. Dosing rats orally for 30 days, then vaginal wall samples were taken to examine vaginal collagen levels with Sirius red staining. The amount of collagen is calculated by the percentage area of ??the collagen pixels compared to the pixels of the entire vaginal tissue. The results show that the mean amount of collagen at P0, P1 and P2 is 55.53 ± 8.12 respectively; 67.50±3.89; 78.14±5.87. The One-way ANOVA test shows statistically significant differences among the groups (p = 0.000). The post hoc analysis using the LSD test finds that the mean amount of vaginal collagen in P2 is the highest than P0 (p=0.000) and P1 (p=0.001) and P1 is higher than P0 (p=0.000). It is concluded that giving of ethanol extract of Hylocereus polyrhizus rind is able to prevent the decrease in vaginal wall collagen in menopausal rats.